Garo spelling and Garo phonology - Burling, Robbins (2024)
Two important books on comparative Sino-Tibetan that were published in the seventies, Paul Benedict's Sino-Tibetan Conspectus (1972) and James A. Uatisoff's Variational Semantics in Tibeto-Burman (1978), cite a number of Garo words in a sufficiently confusing transcription to remind me that the available data on this language (Bodo Group of Northeastern India) can be misleading to those who have not worked with it themselves. It may be useful, there¬fore, to offer a few notes about conventional Garo spelling (as used, for instance, in Garo dictionaries) and about the relevant aspects of Garo phonology, so that Tibeto-Bur-manist- can make the best use of available Garo materials. In order to keep things sorted out, I will use " " for spellings used by Benedict or Matisoff; underlining for conventional Garo spelling; ] for a transcription with more phonetic detail than is needed either for practical spelling or for abstract phonological purposes; and / / for examples in a more abstract phonological form--the more or less "phonemic" transcription that, I suggest, would be most useful for comparative purposes.